IMPLEMENTASI KURIKULUM ISMUBA DALAM MENINGKATKAN KETERAMPILAN, SIKAP DAN PENGETAHUAN SISWA DI SD MUHAMMADIYAH SLANGGEN - Faizah Ayu Yuniarti; Hafidh Nur Fauzi; Hendro Widodo (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2020)
ABSTRACTThe implementation of the Al-Islam curriculum, Kemuhammadiyahan and Arabic(ISMUBA) has very different characteristics from the general curriculum. there are stillmany obstacles that are found that greatly affect learning outcomes both learning mediaand assessment that are more complicated. then the method used in learning has notbeen effective and in accordance with learning material. This research method is amethod of classroom action research conducted in improving the learning process, withfour meetings. The assessment taken in this study is an evaluation of the evaluation ofeach meeting in the form of attitudinal value, knowledge value and skill value guided bythe teacher's book in chapter three